ULF GEOMAGNETIC PERTURBATIONS DUE TO SEISMIC NOISE PRODUCED BY ROCK FRACTURE AND CRACK FORMATION TREATED AS A STOCHASTIC PROCESS - Surkov V.V.; Hayakawa M. (My University, 2006)
A mechanism of ULF geomagnetic field perturbations caused by rock fracture and tectonic activity is studied. It is assumed that the rock fracture is accompanied by crack-generated seismic emission due to cracks pile up at underground cracked zones. Temporal series of seismic impulses due to the crack growth is supposed to be a stationary random process, which obeys Poisson distribution. The seismic emission of the cracks results in excitation of electric current due to motion of the conductive ground in the geomagnetic field, that is so-called diamagnetic effect in moving conductors immersed in the external magnetic field. The electric currents build up as a result of the random displacements in the conductive rock, which in turn leads to the random perturbations of the geomagnetic field. Acoustic wave field derivable from the crack seismic moment is used in order to obtain the electromagnetic variations due to growth of single crack. Averaging of these variations over random crack plane orientation and over crack sizes gives an assessment of mean level of the electromagnetic noise produced by the evolution of the crack ensemble. This assessment is consistent in magnitude with the ULF electromagnetic variations recorded prior to and after some strong earthquakes. © 2006 Elsevier Ltd. All rights reserved.
Keywords: ACOUSTIC EMISSION; EARTHQUAKE PREDICTION; GROUND CONDUCTIVITY; MAGNETIC MOMENT; RANDOM PROCESS; ROCK FRACTURE; SEISMIC MOMENT; ULF GEOMAGNETIC PERTURBATION